2015
DOI: 10.1007/s00408-015-9727-5
|View full text |Cite
|
Sign up to set email alerts
|

Value of Cardiac Troponin and sPESI in Treatment of Pulmonary Thromboembolism at Outpatient Setting

Abstract: We observed that patients with acute PTE, low-risk sPESI, and negative troponin levels can be safely treated in the outpatient settings. Also the presence of cancer alone does not necessitate hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
0
1
2
Order By: Relevance
“…In our study, the overall mortality rate was around 13%, and no change was observed in the mortality rate over the years. The mortality rate was found to be 13% in our two prospective studies between 2008 and 2009 and between 2012 and 2014 [5,6]. However, while the PTErelated mortality rate was 5.6% in our first study, it was 4.4% in the other one.…”
Section: Discussioncontrasting
confidence: 54%
“…In our study, the overall mortality rate was around 13%, and no change was observed in the mortality rate over the years. The mortality rate was found to be 13% in our two prospective studies between 2008 and 2009 and between 2012 and 2014 [5,6]. However, while the PTErelated mortality rate was 5.6% in our first study, it was 4.4% in the other one.…”
Section: Discussioncontrasting
confidence: 54%
“…Tolv studier oppfylte kriteriene (8,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). To var randomiserte kliniske studier (17,21), mens resten var observasjonsstudier.…”
Section: Resultaterunclassified
“…Det er også grunn til å tro at kriteriene kan utbedres. Eksempelvis har studier vist at nytteverdien til forenklet PESI (sPESI) kan forbedres ved å integrere målinger av serumtroponiner, serum-natrium og/eller serum-bikarbonat i nyere modeller (18,30,31). Dette indikerer rom for videre optimalisering, men siden funnene ikke er reprodusert i større kliniske studier, mangler de dokumentasjon for bruk i klinisk praksis.…”
unclassified